Comparative study of Helicobacter pylori eradication rates of concomitant therapy vs modified quadruple therapy comprising proton‐pump inhibitor, bismuth, amoxicillin, and metronidazole in Korea. Issue 2 (25th January 2018) - Choe, Jung Wan; Jung, Sung Woo; Kim, Seung Young; Hyun, Jong Jin; Jung, Young Kul; Koo, Ja Seol; Yim, Hyung Joon; Lee, Sang Woo
Abstract: Background: The standard triple Helicobacter pylori regimen now shows unacceptably low treatment success in Korea. Administration of the concomitant therapy for 10 days, which has a high cure rate, is recommended as an alternative first‐line treatment in areas of high clarithromycin resistance including Korea. Recently, modified bismuth‐containing quadruple therapy with amoxicillin (PAM‐B therapy) showed excellent results, regardless of dual clarithromycin and metronidazole resistance. This study compared the concomitant therapy with PAM‐B therapy as a first‐line treatment for H. pylori infection. Method: Subjects infected with H. pylori and naïve to treatment were performed a head‐to‐head comparison between 10‐day concomitant therapy [rabeprazole 20 mg, amoxicillin 1 g, clarithromycin 500 mg, and metronidazole 500 mg twice daily] and 14‐day PAM‐B therapy [rabeprazole 20 mg, amoxicillin 1 g, metronidazole 750 mg, and tripotassium dicitrato bismuthate 600 mg (elemental bismuth 240 mg) twice daily]. Six weeks after treatment, H. pylori eradication was assessed. Results: Two hundred and seventy subjects were randomized. Both regimens achieved high cure rates: 83.0% (112/135) and 88.1% (119/135) by the intention‐to‐treat analysis and 95.5% (106/111) and 96.6% (114/118) by the per‐protocol analysis, respectively. The intention‐to‐treat and per‐protocol analyses revealed no statistically significant difference in the eradication rate ( P  = .299 and P  = .743, respectively). Rates of adverse events were similar between groups (25.2% vs 23.0%, P ‐value: .776) Adverse events, which resulted in poor compliance, occurred in six patients of each group, but there were no serious complications. Conclusions: PAM‐B therapy is as effective as concomitant therapy for eradicating H. pylori with comparative safety. PAM‐B therapy is regarded as a promising alternative to standard triple therapy for a first‐line eradication in Korea.